Correlation between Troponin I Levels and Location of Acute Myocardial Infarction in ST-Elevation Myocardial Infarction Patients - Tiara Monica; Valentin Widry Enggal (HM Publisher, 2025)
Background: Acute myocardial infarction (AMI) remains a leading cause of mortality in Indonesia. Cardiac troponin I (cTnI) is a highly sensitive and specific biomarker for AMI, and its levels may correlate with infarct location and prognosis. This study investigated the relationship between cTnI levels and the location of myocardial infarction in ST-elevation myocardial infarction (STEMI) patients. Methods: A cross-sectional study was conducted on 57 STEMI patients admitted to H. Abdul Manap Regional General Hospital in Jambi City from April 2022 to 2024. Patients were consecutively enrolled based on inclusion and exclusion criteria. cTnI levels were measured using a point-of-care testing (POCT) device. The correlation between cTnI levels and infarct location was analyzed using the Pearson correlation test. Results: The majority of patients were male (78.49%). The highest incidence of AMI was observed in the anterolateral location, with an average cTnI level of 12.16 ng/ml. A strong positive correlation was found between cTnI levels and the location of infarction (r = 0.891, p < 0.05). Conclusion: Higher cTnI levels are associated with specific AMI locations, particularly anterolateral infarctions. This finding highlights the importance of cTnI measurement in assessing AMI severity and potential prognosis.